The implications of climate-related mobility for human security in Vietnam's Mekong Delta: A scoping review - Dung Phuong Le; Melgar, Adriana; Savelli, Adam (Alliance of Bioversity International and CIAT and ILRI, 2022)
The study—part of the CGIAR Initiative: Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience —explores the linkages between climate related mobility and human security in Vietnam’s Mekong Delta (VMD) region. By examining the available evidence through a systematic literature review, the results of previous studies are mapped an analyzed. Evidence gaps and opportunities for future research on climate-related mobility and human security in the VMD are then articulated.